Pesticides: use with care - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The Govermnent of Dominica has adopted a vigilant stance on pesticide imports and usage in the country. A Pesticide Control Board is responsible for registering and licensing approved agrochemicals for import, while the Ministry of Agriculture has...